A chiral analog of the bicyclic guanidine TBD: synthesis, structure and Brønsted base catalysis - Goldberg, Mariano; Sartakov, Denis; Bats, Jan W.; Bolte, Michael; Göbel, Michael W. (Beilstein Journal of Organic Chemistry, 2016)
Starting from (S)-β-phenylalanine, easily accessible by lipase-catalyzed kinetic resolution, a chiral triamine was assembled by a reductive amination and finally cyclized to form the title compound 10. In the crystals of the guanidinium benzoate salt the six membered rings of 10 adopt conformations close to an envelope with the phenyl substituents in pseudo-axial positions. The unprotonated guanidine 10 catalyzes Diels–Alder reactions of anthrones and maleimides (25–30% ee). It also promotes as a strong Brønsted base the retro-aldol reaction of some cycloadducts with kinetic resolution of the enantiomers. In three cases, the retro-aldol products (48–83% ee) could be recrystallized to high enantiopurity (≥95% ee). The absolute configuration of several compounds is supported by anomalous X-ray diffraction and by chemical correlation.
Keywords: absolute configuration; anthrone; cycloaddition; kinetic resolution; lipase